Pengaruh Pengalaman Pelanggan, Kualitas Pelayanan, dan Fasilitas Terhadap Loyalitas Pelanggan Kafe Kopi Ogut Tangerang - Naomi Novitasari Pane; Andy Andy (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to examine customer experience, service quality and facilities on customer loyalty ogut coffee cafe Tangerang. This research is a quantitative study that describes and explains the effect of customer experience, service quality, and facilities on customer loyalty ogut coffee cafe Tangerang. The subjects of this study included buyers at ogut coffee cafe Tangerang, where this study used random sampling techniques with 130 respondents. Data collection techniques that researchers use through surveys, interviews, and direct observation to obtain information directly from the source. Meanwhile, secondary data collection was carried out by researchers using the method of distributing questionnaires and direct observation at the research location, where questionnaires were distributed randomly to 130 respondents. Data were analyzed using SPSS software version 25. Data testing techniques in this study include validity test, reliability test with Cronbach's alpha method, and multiple linear regression analysis to test and verify the research hypothesis.